What makes extra care housing an appropriate setting for people with dementia? An exploration of staff decision-making. (July 2019) - Verbeek, Hilde; Tucker and, Sue; Wilberforce, Mark; Brand, Christian; Abendstern, Michele; Challis, David
Extra care housing facilities in the UK are intended to offer a community-based alternative to care home placement. However, little is known about staff's views of the appropriateness of extra care housing for people with dementia. This paper describes a mixed-methods study which explored this issue using statistical modelling of frontline staff's recommendations of the best care setting for care home entrants; thematic analysis of transcripts from a simulated Resource Allocation Management Panel meeting; and content analysis of care coordinators' reasons for not considering extra care housing in actual care home applications. Frontline practitioners saw extra care housing as a valuable alternative for a significant minority of care home entrants. However, extra care housing was not recommended if people needed care at night. Social care managers expressed general support for the idea of extra care housing, but appeared overwhelmingly focused on maintaining people at home and unsure where in the care pathway extra care housing sat. More evidence is needed on whether extra care housing can be an alternative to care homes and how services should be arranged to meet the needs of people living in extra care housing.